What Obstetricians Need to Know about Crohn’s Disease—A Narrative Review - Bianca Mihaela Danciu; Augustin Marian Marincaş; Mihai Ciocîrlan; Anca Angela Simionescu (Clinical and Experimental Obstetrics & Gynecology)
Objective: Crohn’s disease (CD) is an immune-mediated inflammatory bowel disease (IBD), which comprises an idiopathic aberrant systemic and local inflammatory response. This response is a result of unknown interactions between the luminal content and the intestinal wall. This article is a review of the current state of knowledge providing information to help obstetricians to manage patients with CD, and to understand the particularities of these patients, with emphasis during pregnancy and postpartum, including recommendation for the birthing methods. It is important to explain the usefulness of the pursue of treatment during pregnancy, taking into consideration the drugs allowed during pregnancy, and addressing the challenges that CD may pose in addition to the physiological adaptations of pregnancy. Mechanism: As both an obstetrician and a gastroenterologist, this topic can be approach from two distinct perspectives. Firstly, how CD influences fertility and pregnancy, and secondly, an exploration on how hormonal changes and immune system tolerance during pregnancy probably influences CD. Findings in Brief: Data shows that pregnancy outcomes are influenced by the clinical course of CD at the time of conception. Latent disease prior to conception is associated with uneventful pregnancies and favorable neonatal outcomes, comparable to general population. Conversely, an active disease during pregnancy and ileal localization can be associated with prematurity, stillbirth, and small-for-gestational age (SGA) infants. A high risk of preeclampsia was reported in pregnancy with severe CD and oral or systemic corticosteroids administration. Optimal management approach involves a multidisciplinary team consisting of an obstetrician, gastroenterologist, and surgeon. Thiopurines and biologic agents are considered safe during pregnancy and breastfeeding. In infants with CD, alteration in the composition of the maternal microbiome may contribute to the systemic inflammation and to influence the transmission of an altered microbiota to the infants. This suggests that modulating the early microbiome can be an effective strategy to reduce cases of CD. Conclusions: Healthcare practitioners and patients must be aware that CD patients can have a successful pregnancy and a healthy infant. A multidisciplinary team can provide supportive care and help address significant information to adapt the treatment plan, and to monitor pregnancy.